Epidermofitosis de los pies (pie de atleta) en estudiantes preuniversitarios - Jiménez-Quirós, Otto (Revista de Biología Tropical, 1959)
A study is presented of the incidence of athlete’s foot In 2012 intrant students of the University of Costa Rica, 1116 male and 896 female. The total number of cases found was 1438 (71.47%). The incidence among men was of 83.51 per cent, that among women of 56.47 per cent. As shown in table 1, incidence was greater in public than in private institutions, and in schools having a swimming pool than in those lacking one. Table 2 shows a classification of lesions, chronic types being most and acute types the least frequent.